Haptoglobin is associated with increased early perihematoma edema progression in spontaneous intracranial hemorrhage. Issue 8 (October 2020) - Halstead, Michael R; Mould, W Andrew; Sheth, Kevin N; Rosand, Jonathan; Thompson, Richard; Levy, Andrew; Hanley, Daniel F; Goldstein, Joshua N; Nyquist, Paul
Introduction: Perihematomal edema in intracranial hemorrhage is influenced by free hemoglobin clearance and inflammation. Serum Haptoglobin (Hp) binds free hemoglobin, affecting heme clearance and free radical production. Of the three Hp phenotypes, Hp 1-1 has the greatest effect on free hemoglobin clearance. Aim: To determine if individuals with Hp 1-1 phenotype have different rates of early perihematomal edema formation as compared to those with Hp 2-1 and Hp 2-2. Methods: We determined Hp phenotype, intracranial hemorrhage volume, and rate of early change in perihematomal volume in participants from three prospectively collected intracranial hemorrhage cohorts. The association of Hp phenotypes 1-1, 2-1, 2-2, with early change in perihematomal volume, while controlling for key clinical characteristics was analyzed using a multivariate model. Findings: One-hundred and sixty-six participants were included: 73 (44%) female, 41 ( 25%) African Americans, 34 (20%) diabetics, 133 (80%) with hypertension, and 75 (45%) active smokers. There were 15 subjects with Hp phenotype 1-1, 86 with 2-1, and 65 with 2-2. In fully adjusted analysis, Hp 1-1 had a significantly increased estimated mean rate of early change in perihematomal volume at 1.15 (95% confidence interval 0.58–1.71) as compared to all other Hp 2-1 or Hp 2-2 containing phenotypes (0.30, 95% confidence interval 0.06–0.54; 0.29 95% CI 0.02–0.56). Neither mortality nor discharge mRS differed between Hp phenotypes. Conclusion: Haptoglobin phenotype is associated with early change in perihematomal volume. Hp 1-1 phenotype had significantly increased mean rate of early change in perihematomal volume within the first 96 h, suggesting that haptoglobin phenotype may be a key player in understanding the multiphasic progression of perihematomal volume in spontaneous intracerebral hemorrhage. A larger prospective observational study is warranted.